2004
DOI: 10.1242/jcs.00855
|View full text |Cite
|
Sign up to set email alerts
|

A role for the cytoskeleton in prolactin-dependent mammary epithelial cell differentiation

Abstract: The function of exocrine glands depends on signals within the extracellular environment. In the mammary gland, integrin-mediated adhesion to the extracellular matrix protein laminin co-operates with soluble factors such as prolactin to regulate tissue-specific gene expression. The mechanism of matrix and prolactin crosstalk and the activation of downstream signals are not fully understood. Because integrins organize the cytoskeleton, we analysed the contribution of the cytoskeleton to prolactin receptor activa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
44
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
6
2
2

Relationship

1
9

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 65 publications
1
44
0
Order By: Relevance
“…Induction of cytoskeleton structuring has been described with many cytokines and chemokines but mostly over longer time spans. Pioneering studies on prolactin receptor (35), growth hormone receptor (36), and epidermal growth factor receptor (37) have suggested that machineries carried by the cytoskeleton might be involved in STAT5 and pSTAT5 distribution and proposed that rapid organization was involved. Here, in our study, we used super-resolution optical microscopy to describe in detail how radial microtubules are formed within a few min of IL-7 activation, bridging plasma and nuclear membranes across the narrow cytoplasm of CD4 T-lymphocytes.…”
Section: Sted Microscopy Analysis Of Il-7-induced Membrane Microdomaimentioning
confidence: 99%
“…Induction of cytoskeleton structuring has been described with many cytokines and chemokines but mostly over longer time spans. Pioneering studies on prolactin receptor (35), growth hormone receptor (36), and epidermal growth factor receptor (37) have suggested that machineries carried by the cytoskeleton might be involved in STAT5 and pSTAT5 distribution and proposed that rapid organization was involved. Here, in our study, we used super-resolution optical microscopy to describe in detail how radial microtubules are formed within a few min of IL-7 activation, bridging plasma and nuclear membranes across the narrow cytoplasm of CD4 T-lymphocytes.…”
Section: Sted Microscopy Analysis Of Il-7-induced Membrane Microdomaimentioning
confidence: 99%
“…However, based on very similar phenotypes, Rac3 appears to be a good candidate to be considered. Connections between PRL, extracellular matrix proteins, and cytoskeleton play a critical role in maintaining mammary cell adhesion, morphology and function (Edwards et al 1998, Zoubiane et al 2004. b-catenin is a multifunctional protein connecting cytoskeleton proteins, and it plays a critical role in Wnt signaling in the mammary gland (Muller et al 2002).…”
Section: Discussionmentioning
confidence: 99%
“…In no culture conditions has there been any significant expression of -lactalbumin (and, consequently, there is no synthesis of lactose), indicating that expression of this protein is regulated by an alternative mechanism within the mammary gland (Lee et al, 1984;Wilde et al, 1984;Bissell & Hall, 1987). More recently, it has been observed that in addition to the presence of ECM, adhesion of the mammary epithelium to ECM is critical for cellular differentiation (Zoubiane et al, 2004). Based on their observations, these authors suggested a role for the integrins in coordinating the cytoskeleton and regulating the induction of cellular differentiation by PRL.…”
Section: Extracellular Matrixmentioning
confidence: 99%